2021
DOI: 10.3390/cancers13081852
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Resistance of Oncogenic RAS-Driven Tumors to Dual MEK and ERK Inhibition

Abstract: Oncogenic mutations in RAS family genes arise frequently in metastatic human cancers. Here we developed new mouse and cellular models of oncogenic HrasG12V-driven undifferentiated pleomorphic sarcoma metastasis and of KrasG12D-driven pancreatic ductal adenocarcinoma metastasis. Through analyses of these cells and of human oncogenic KRAS-, NRAS- and BRAF-driven cancer cell lines we identified that resistance to single MEK inhibitor and ERK inhibitor treatments arise rapidly but combination therapy completely bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Murine models have demonstrated activity of MEK inhibition alone in other HRASmt diseases, such as Costello syndrome [52]. Finally, mTOR inhibitors combined with ERK inhibition demonstrated activity against HRASmt G12V-driven autochthonous sarcoma [53]. Given the current approval of everolimus in the advanced/metastatic HR+ BC setting [54], future analyses may consider determining if HRASmt cancers serve as a predictor of response.…”
Section: Discussionmentioning
confidence: 99%
“…Murine models have demonstrated activity of MEK inhibition alone in other HRASmt diseases, such as Costello syndrome [52]. Finally, mTOR inhibitors combined with ERK inhibition demonstrated activity against HRASmt G12V-driven autochthonous sarcoma [53]. Given the current approval of everolimus in the advanced/metastatic HR+ BC setting [54], future analyses may consider determining if HRASmt cancers serve as a predictor of response.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that Akt and p53 might be potential host therapeutic targets [ 46 ]. Array-based kinome profiling revealed that signals were rewired in resistant cells, and the results were confirmed by Western blots [ 47 ]. Furthermore, signaling pathways with spatial resolution have been achieved by analyzing the kinome in subcellular partitioning [ 48 ].…”
Section: Technologies For Kinome Analysismentioning
confidence: 99%
“…Similarly, Catalano et al showed that dual inhibition of MEK and Erk represented anti-tumor efficacy and blocked the emergence of drug resistance in an HRAS G12C -driven autochthonous sarcoma model. However, this combination could not be successful to revert previously developed resistance, which offers the use of dual MEK and Erk treatment as a first-line therapy [140]. In addition to these, the authors noted that some cell lines resistant to combined MEK and Erk inhibition showed dependency on MAP4K4 activity, which serves MAP4K4 as a potential new therapeutic target [140].…”
Section: Erk Inhibitorsmentioning
confidence: 99%
“…However, this combination could not be successful to revert previously developed resistance, which offers the use of dual MEK and Erk treatment as a first-line therapy [140]. In addition to these, the authors noted that some cell lines resistant to combined MEK and Erk inhibition showed dependency on MAP4K4 activity, which serves MAP4K4 as a potential new therapeutic target [140]. Despite these successful examples of dual MEK and Erk inhibition in some RAS-mutant models, the potential of these combinations for clinical implementation awaits further investigation.…”
Section: Erk Inhibitorsmentioning
confidence: 99%